Restoration seed banks-a matter of scale - Merritt, D.; Dixon, Kingsley (2011)
With nearly two-thirds of the world's ecosystems degraded (1), the October 2010 meeting of the Conference of the Parties to the Convention on Biological Diversity (COP-10) highlighted ecological restoration as a significant opportunity for achieving global conservation goals (2). The restoration of nature, natural assets, and biodiversity is now a global business worth at least $1.6 trillion annually and likely to grow substantially (3). Although seed banks have emerged as a tool to protect wild plant species (4), off-site (ex situ) conservation measures at seed banks must be complementary to “on the ground” management at the conservation site. For example, whereas global targets are for restoration or management of at least 15% of each ecological region or vegetation type (1, 5), recognition of the mechanisms required to achieve these goals is largely absent from policies.